2008
DOI: 10.3346/jkms.2008.23.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Pre-engraftment Syndrome in Hematopoietic Stem Cell Transplantation

Abstract: The clinical findings of fever and skin rash with or without evidence of fluid retention, which mimic engraftment syndrome, have been observed during the pre-engraftment period in patients undergoing hematopoietic stem cell transplantation. In order to characterize this newly observed clinical syndrome called pre-engraftment syndrome (pES), we retrospectively analyzed the clinical records of 50 patients. Three out of 14 patients (23.1%) who underwent cord blood stem cell transplantation developed non-infectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…[41][42][43][44][45][46] PES is reported after conventional and RIC transplants. Data are conflicting as to whether acute GVHD incidence is increased in persons with prior PES and whether PES influences NRM and survival.…”
Section: Pre-es (Pes) After Umbilical Cord Blood Transplantationmentioning
confidence: 98%
“…[41][42][43][44][45][46] PES is reported after conventional and RIC transplants. Data are conflicting as to whether acute GVHD incidence is increased in persons with prior PES and whether PES influences NRM and survival.…”
Section: Pre-es (Pes) After Umbilical Cord Blood Transplantationmentioning
confidence: 98%
“…[8][9][10][11] Although the pathogenesis was poorly understood, pre-ES could have developed long before neutrophil engraftment, of which the cumulative incidence was generally higher than that of ES, due to less stringent diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Furthermore, pre-engraftment syndrome (pre-ES), which is more emphasized with a fever, rash and an occurrence in the pre-engraftment period, has been described and considered different from ES. [8][9][10][11] We retrospectively analyzed the clinical records of 176 patients following allogeneic HSCT. Furthermore, in a comparative study of the clinical features of pre-ES and ES patients, we found that both clinical syndromes were similar, which could be defined as a new entity of a clinical syndrome, termed as peri-engraftment syndrome (peri-ES).…”
Section: Introductionmentioning
confidence: 99%
“…One author defined engraftment as "the first appearance of neutrophils the peripheral blood" (Maiolino et al, 2003, p. 394), and other authors defined engraftment as an elevated number of neutrophils over an extended period of time. Kanda et al (2013) defined engraftment as an ANC count of greater than or equal to 500 mcl for three consecutive days, some authors defined it as an ANC count of greater than 500 mcl for three consecutive days (Hong et al, 2013;GonzĂĄlez-Vicent et al, 2004;Schmid et al, 2008), and others defined it as an ANC count of greater than 500 mcl for two consecutive days (Capizzi et al, 2001;Carreras et al, 2010;Lee et al, 2008). Some authors particularly noted that engraftment begins on the first day of the consecutive days of specific ANC counts (Carreras et al, 2010;Hong et al, 2013;Kanda et al, 2013;Schmid et al, 2008).…”
Section: Definitionsmentioning
confidence: 99%
“…Because of a lack of definitive diagnostic criteria, reports on the incidence of ES vary from 10%-77% (Gorak et al, 2005;Hong et al, 2013;Kanda et al, 2013;Lee, Lim, Kim, Kim, & Lee, 2008;Schmid, Stachel, Pagel, & Albert, 2008). The presence of ES has been linked to increased mortality and longer length of hospitalization (Gorak et al, 2005;Maiolino et al, 2003), and early identification and treatment has been shown to result in improved clinical outcomes (Capizzi et al, 2001;Carreras et al, 2010;Gorak et al, 2005;Maiolino et al, 2003;Spitzer, 2001).…”
Section: Introductionmentioning
confidence: 97%